Assessing the Impact of Electric Vehicle Fleets on a Multi-Microgrids System Under Different Operating Modes - Mabrouk, Elmehdi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Global climate change and the lack of fossil fuels reserves have already had observable effects on the environment. Therefore, an undeniable investment is being made to respond these heavy challenges and to accelerate the momentum towards further embracing the electrification of transportation in smart microgrids, energy efficiency and clean energy production. The paper presents a novel cost-effective management of non-renewable resources of a multi-microgrid system under different operating modes (islanded, connected) with integrating renewable energy sources. Also, we investigate the impact of controlling vehicle-to-grid (V2G) operations on the multi-microgrid system by establishing a coordinated charging control strategy for plug-in electric vehicles (PEVs) with the aim of obtaining the maximum benefit from the grid as well as minimize the overall operating cost of the system. Both, the management of the multi-microgrid system and the EVs charging strategy have been formulated and solved using the Genetic Algorithm (GA), where the obtained results have shown that this method increases the quality, and the efficiency of obtained day-ahead scheduling solutions under any operating mode.